Orthotic intervention for the hand and upper extremity : splinting principles and process - Austin, Noelle M.; Jacobs, MaryLynn A. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2014)
'Entry-level occupational therapists are expected to have fundamental skills in splinting theory, design, and fabrication. As occupational therapy students, they gain these skills through didactic courses, fieldwork, or observations. Orthotic Intervention of the Hand and Upper Extremity: Splinting Principles and Process, Second Edition, delivers just that. Instructors need materials to teach students how to apply theory to practice in the area of splinting. This book provides instructors with the pedagogical framework necessary to help students, inexperienced therapists, and expert hand therapists make the right decision whether to fabricate a thermoplastic or neoprene splint, cast, tape, or choose an over-the-counter splint for their patient. This detailed and easy-to-use reference demonstrates splint fabrication techniques and related interventions for the upper extremity and highlights anatomical and biomechanical principles specifically related to splints'--Provided by publisher.
Concepts of orthotic fundamentals / by MaryLynn Jacobs and Jerry Coverdale -- Anatomical principles / by Noelle M. Austin -- Tissue healing / by Richard A. Bernstein -- Mechanical principles / by Gary P. Austin -- Equipment and materials / by Noelle M. Austin -- Fabrication process / by Noelle M. Austin -- Immobilization orthoses -- Mobilization orthoses -- Restriction orthoses -- Nonarticular orthoses -- Prefabricated orthoses / by Rebecca Harris -- Casting / by Karen Schultz, updated by MaryLynn Jacobs -- Taping techniques / by Ruth Coopee -- Neoprene orthoses / by Sabrina Cassella and Jessica Griffin Scheff -- Stiffness / by Karen Schultz, updated by MaryLynn Jacobs -- Fractures / by Jennifer Stephens Chisar and Nancy Chee -- Arthritis / by MaryLynn Jacobs, Shrikant Chinchalkar, and Joey Pipicelli -- Tendon injuries / by Alexandra MacKenzie -- Peripheral nerves injuries / by MaryLynn Jacobs -- The athlete / by Kimberly Goldie Staines and Evan D. Collins -- Adult neurologic dysfunction / by Salvador Bondoc -- The pediatric patient / by Jill Peck-Murray -- Burns / by Reg Richard and Jonathan Niszczak -- The musician / by Colleen Lowe -- Hand and upper extremity transplantation / by Marie Pace and Kimberly Zeske-Maguire.
Preceded by: Splinting the hand and upper extremity : principles and process / [edited by] MaryLynn A. Jacobs, Noelle M. Austin. c2003.
Includes bibliographical references and index.
Keywords: Arm Injuries -- rehabilitation; Hand; Split; Hand Injueris -- rehabilitation; Orthotic Devices